(untitled) (Fiep Bulletin - online, 2011)
A lot of discussions aroused about the real gain of flexibility with the practice of the Pilates method, and as it is known, the flexibility has extreme importance for a better quality of life. In this paper we tried to measure the real gain of flexibility provided by the practice of the Pilates method with the instrument patented and called FORM MOVE strings, because there is few scientific papers concerning the flexibility and Pilates method up to the present time and also few resources in the development of new accessories to encourage the practice of physical exercises and the gain of flexibility. The sample was composed by a group of 12 people, aging between 18 to 32 years old, average height of 1.65m and average weight of 62.0 kg for women and 69.0 Kg and 1.79m for men. An initial data collecting was accomplished, and another one after 10 weeks of practice of Pilates method, the control groups that had been practicing the method for more than 6 months in the three modalities were evaluated in the beginning of the research by the evaluator who was prepared by the researcher, this person did not know which modality were practice by the volunteers. In the modalities the proposed exercises varied only in the type of application (Mat, studio, Water Pilates), they were part of the training of the control groups. The instrument used to make the flexibility collecting was the Wells bench. The results demonstrated the efficiency of the association of strings with the method in the flexibility gain, with even higher results in the hydrotherapy (Water Pilates modality) due to the physiological effects of immersion and the possible maintenance of stretching that the developed instrument can have in the accomplishment of the proposed exercises.